In Silico Screening of Pyridine Derivatives as Potential DHFR Inhibitors for Anticancer Activity - NERKAR, A.G.; GHONE, S.A.; SAREEN, A.; MEHTA, A.; BHAGAT, S.A.; MOHANRAJ, K.P.; THAKER, A.K. (Asian Journal of Chemistry, 2010)
In this paper, in silico screening prioritization of some pyridinyl Schiff bases (Schiff bases of isoniazid (INH)) as inhibitors of mammalian dihydrofolate reductase enzyme (DHFR) for anticancer activity, before actual synthesis of the molecules and anticancer evaluation are reported.